A treatment of wastewater containing basic dyes by the use of new strain Streptomyces microflavus CKS6. (1st April 2017) - Buntić, Aneta V.; Pavlović, Marija D.; Antonović, Dušan G.; Šiler-Marinković, Slavica S.; Dimitrijević-Branković, Suzana I.
Abstract: This study has investigated the biodegradable potential of the Streptomyces microflavus CKS6 growing microbial cells for the colored waste water treatment. The Crystal violet and Safranin T basic dyes have been employed as a model compounds for decolorization evaluation by exploring the correlation with the other rate-dependent environmental parameters. Through the measuring of color reduction by UV–Vis spectroscopic monitoring analysis, the results revealed well operational properties of Streptomyces microflavus CKS6 for the successful refinement of dyes contaminate water solutions. Optimized process parameters were found to be apparently mild, involving the use of the reaction temperature of 27–30 °C and pH 6–7. With the lower dye concentrations, the decolorization efficiency was found to be more effective and rapid, wherein the 1 mg/L of Crystal violet was removed within the 2.5 h of the treatment time, while the solution with the same content of the Safranin T dye required 30 h. A possible mechanism for the working medium decolorization was accomplished in two consecutive steps, by the primarily dye adsorption onto the bacterial cells surface, followed to biodegradation by the active microbial enzymatic system, wherein the lignin peroxidase acts a notable role. The phytotoxicity analysis of the degradation products revealed less toxicity to the plants, compared to parental chemicals. In addition, the adaptation of individual dye optimized parameters was effectively implemented in the real waste water system containing the mixture of these two dyes. The overall results may postulate that Streptomyces microflavus CKS6 may be promising applicants for dye contaminated water treatment. Graphical abstract: Highlights: Biological treatment of waste water containing basic dyes. Strong biodegradation potential of new strain Streptomyces microflavus CKS6. Active participation of lignin peroxidase during the process of dye degradation. Less phytotoxicity of biodegradation products compared to parental chemicals.